2018
DOI: 10.1159/000494391
|View full text |Cite
|
Sign up to set email alerts
|

Cubilin Single Nucleotide Polymorphism Variants are Associated with Macroangiopathy While a Matrix Metalloproteinase-9 Single Nucleotide Polymorphism Flip-Flop may Indicate Susceptibility of Diabetic Nephropathy in Type-2 Diabetic Patients

Abstract: Aim: Aim of this study was to investigate the association of genetic variants of functional polymorphisms of matrix metalloproteinase and Cubilin (CUBN) with diabetic nephropathy (DN), end-stage renal disease (ESRD), and risk of cardiovascular disease (CVD) in Caucasian type 2 diabetes (T2D) patients. Methods: 472 T2D-patients were genotyped for 3 single-nucleotide polymorphisms (SNPs; MMP-2 [rs2285053], MMP-9 [rs17576] and CUBN [rs1801239]). Genotyping was carried out by allelic discrimination using TaqMan SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In a meta-analysis of genome-wide association studies in 5825 patients with DM and 46,061 controls, polymorphisms in the gene encoding cubilin were associated with urinary albumin excretion [ 99 ]. In a smaller study ( n = 472 patients with T2DM) cubilin gene variants were associated with increased risk for both ESRD and peripheral arterial disease [ 100 ].…”
Section: Cubilinmentioning
confidence: 99%
“…In a meta-analysis of genome-wide association studies in 5825 patients with DM and 46,061 controls, polymorphisms in the gene encoding cubilin were associated with urinary albumin excretion [ 99 ]. In a smaller study ( n = 472 patients with T2DM) cubilin gene variants were associated with increased risk for both ESRD and peripheral arterial disease [ 100 ].…”
Section: Cubilinmentioning
confidence: 99%
“…Many of these studies have been conducted in populations of a specific ethnic origin, so their relevance has a local or geographical character, depending on the size and characteristics of the population included in the study. Several studies analyze the association of gene polymorphisms with cardiovascular disease in the Caucasian population [25][26][27] . These and many other studies show that the presence of polymorphic variants in numerous genes involved in cardiovascular regulation may favor the risk or predisposition to a broad spectrum of cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, an independent and much larger GWAS study of 3431 patients with breast cancer found significant association ( p = 4.1 × 10 −6 ) but with the opposite allele. This is highly relevant for transfer to the clinic, and we note here that there are many examples in the literature with a flip-flop effect in which the opposite alleles of the same variant are associated with increased risk of disease, which occur when the investigated variant is correlated with the true causative/functional variant through interactive effects or linkage disequilibrium which differs between populations [ 57 , 58 , 59 , 60 ]. Therefore, what may be required to truly move this gene towards clinical guidance is additional fine mapping and exon sequencing across different populations of patients with anthracycline-induced heart failure.…”
Section: Genetic Variants Associated With Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%